Propylene Yield from Olefin Plant Utilizing Box-Cox Transformation in Regression Analysis - Zakria Mohamad Hafizi; Mohd Nawawi Mohd Ghazali; Abdul Rahman Mohd Rizal (E3S Web of Conferences, 2021)
Propylene yield is one of the key operating parameters that is monitored daily in the running olefin plant. This study was conducted in the actual world-scale olefin plant to measure the impact of identified controlled variables on the propylene yield. The Box-Cox data transformation was adopted in the Regression Analysis using Minitab Software Version 18 due to non-normal data were observed after normality and stability test were conducted using Box Plot, I-MR Chart, Run Chart, Graphical Summary, and Normality Plot tools. The model concluded that propylene yield in the studied plant was contributed by the factors of -0.000243 Hearth Burner Flow, 0.01332 Integral Burner Flow, and 0.08598 Naphtha Feed Flow. The Response Optimizer tool also suggested that the propylene yield from naphtha liquid feed can be maximized at 11.22% with the control setting at 10,993.86 kg/hr of Hearth Burner Flow, 604.61 kg/hr of Integral Burner Flow, and 63.50 t/hr of Naphtha Feed Flow.